Performance Comparison of 28 GHz Rectangular Patch Antenna Based on Three Different Dielectric Constant Substrates for 5G Communications (The International Journal of Engineering & Information Technology (IJEIT), 2023)
This article introduces a design and analysis of three inset-fed rectangular patch antennas based on three different dielectric constant substrate materials. These substrate materials include Rogers RT-5880, Preperm 260 LDS, and Polycarbonate. The introduced structures are resonant at a frequency of 28 GHz and employ copper material for a radiating patch on the top of the dielectricsubstrate and a ground plane on the bottom of the substrate. The design dimensions of the three structures have been calculated, while the three materials employed as the substrate in the three antenna structures are different. Furthermore, Computer Simulation Technology (CST) software was employed to simulate and compare the performance of the three introduced designs. The performance indexes used to evaluate and compare the performance of the three proposed designs include realized gain, return loss, radiation efficiency, bandwidth, radiation pattern, and voltage standing wave ratio